Creep Phenomenon in Thrust Washers of Needle Roller Bearings - Hiromichi Takemura; Taketoshi Chifu; Tetsuya Okumura (Tribology Online)
In radial rolling bearings, a phenomenon called creep occurs in the outer ring (the stationary/fixed raceway) when the bearing is subjected to excessive load. This study aims to investigate creep in the fixed thrust washers of thrust rolling bearings, a different bearing type designed to support axial loads. We examined the behavior of creep in thrust needle roller bearings with washers of various thicknesses and then compared results to those found through FEM analysis. The results showed that creep in the fixed raceway of thrust rolling bearings is similar to that in radial rolling bearings [1], with rolling friction having little effect and applied thrust load and raceway thickness having substantial impacts.